AB0542 Early reduction in synovitis and bone EDEMA evaluated by MRI in tocilizumab-treated RA patients with inadequate response to anti-TNF. (23rd January 2014) - Lisbona, M.; Maymo, J.; Pàmies, A.; Ares, J.; Solano, A.; Almirall, M.; Sanchez, S.; Carbonell, J.
Abstract : Objectives: To evaluate early effects of tocilizumab (TCZ) on synovitis, bone edema and tenosynovitis by hand MRI in patients with active RA and inadequate response to anti-TNF. Methods: Patients with active RA (DAS28 ≥3.2), synovitisin at least 1 dominant hand joint and inadequate responders to anti-TNF, received TCZ (8 mg/kg iv) every 4 weeks in monotherapy or added to previous DMARD. 1.5T MRI of dominant hand (metacarpophalangeal joints 2-5) and wrist was acquired at baseline and after TCZ (± week 10). MRIs were scored by 2 independent readers using RAMRIS method blinded to image chronology and clinical data. Clinical improvement was assessed by conventional outcome measures. Changes from baseline to week 10 was tested using the paired Student's T-test. The SPSS version 15.0 for windows was used for the statistical analysis. Results: 22 patients (20 women, mean age 56.2±10.7 years, 68.7% rheumatoid factor positive, 77.3% for ACPA and 95.5% had erosive disease) with a meandisease duration of 12.2±7.1 years were included. Twelve of 20 patients started TCZ associated with standard DMARD therapy (6 methotrexate, 4 leflunomide, 2 hydroxychloroquine) and 86.2% were taking oral prednisone (mean 8.0±5.7 mg day). Statistically significant decrease in the mean of the scores of synovitis and bone edema was observed after 3 doses of TCZ. Mean of tenosynovitis score also decreased while scoring of erosions in MRI did not change. A significant statistical improvement of the variables of clinical activity (DAS28, SDAI, CDAI, SJC66, TJC68, VAS pain), in laboratory variables (ESR, CRP) and functional capacity (HAQ) was observed after treatment with TCZ (Table 1 ). Conclusions: TCZ significantly decreased synovitis and bone edema on MRI in active RA patients with an inadequate response to anti-TNF and was also effective in reducing clinical activity and disability. Disclosure of Interest: None Declared